FILTRATE Syzygium polyanthum AND MONOCYTES OF PERIPHERAL BLOOD WHITE RAT (Rattus norvegicus) WISTAR’S STRAIN WITH HYPERLIPIDEMIA - Sundayani, Lina; Farida, Farida; Diarti, Maruni Wiwin (Jurusan Analis Kesehatan, Poltekkes Kemenkes Mataram, 2014)
AbstractSyzygium polyanthu) contain cumpounds that can lower cholesterol leavels and then inhibit the formation of free radicals and suppress the inflammatory response of injured endotel. In this study, monocyte count is the parameter of progression of atherosclerosis. The purpose of this study is to determine the potential of the leaves preparation filtrate (Syzygium polyanthum) to the number of monocytes in the blood wistar strain (Rattus norvegicus) rat with hyperlipidemia. This research design using a completely randomized design. The sample size in this study were 30 mice and devided into 6 treatment groups, K1: negatif control,K2: positive control, K3,K4,K5 and K6 is the treatment group. The result shown the average cholesterol level 87.5 ± 13.9 mg/dl and the number of monocytes 6 in peripheral blood of white rat wistar strain (Rattus norvegicus) before having hyperlipidemia. The mean cholesterol level 199.7 ± 22.1 mg/dl and the number of monocytest 4 in peripheral blood of white rat wistar strain (Rattus norvegicus) after hyperlipidemia. The mean cholesterol 91.6 ± 11.8 mg/dl and the number of monocytes 3 in peripheral blood of white rat wistar strain (Rattus norvegicus) in hyperlipidemia and after had treated with preparation filtrate concentration 25%, 50%, 75%, 100 %. The One Way Anova statistic result generate value p=0.000<α0.05. The conclution of this study is filtrate of Syzygium polyanthum has effect to the number of peripheral blood monocytes in experimental animals wistar strain white (Rattus norvegicus) rat with hyperlipidemia.Key woods : Hyperlipidemia, Monocytes, Syzygium polyanthum